Blockade of Acid-Sensing Ion Channels Increases Urinary Bladder Capacity With or Without Intravesical Irritation in Mice - Yoshiyama, Mitsuharu; Kobayashi, Hideki; Takeda, Masayuki; Araki, Isao (Frontiers in Physiology, 2020)
We conducted this study to examine whether acid-sensing ion channels (ASICs) are involved in the modulation of urinary bladder activity with or without intravesical irritation induced by acetic acid. All in vivo evaluations were conducted during continuous infusion cystometry in decerebrated unanesthetized female mice. During cystometry with a pH 6.3 saline infusion, an i.p. injection of 30 µmol/kg A-317567 (a potent, nonamiloride ASIC blocker) increased the intercontraction interval (ICI) by 30 % (P<0.001), whereas vehicle injection had no effect. An intravesical acetic acid (pH 3.0) infusion induced bladder hyperactivity, with reductions in ICI and maximal voiding pressure (MVP) by 79 % (P<0.0001) and 29 % (P<0.001), respectively. A-317567 (30 µmol/kg i.p.) alleviated hyperreflexia by increasing the acid-shortened ICI by 76 % (P<0.001). This dose produced no effect on MVP under either intravesical pH condition. Further analysis in comparison with vehicle showed that the increase in ICI (or bladder capacity) by the drug was not dependent on bladder compliance. However, intravesical perfusion of A-317567 (100 µM) had no effect on bladder activity during pH 6.0 saline infusion cystometry, and drug perfusion at neither 100 µM nor 1 mM produced any effects on bladder hyperreflexia during pH 3.0 acetic acid infusion cystometry. A-317567 has been suggested to display extremely poor penetrability into the central nervous system and thus to be a peripherally active blocker. Taken together, our results suggest that blockade of ASIC signal transduction increases bladder capacity under normal intravesical pH conditions and alleviates bladder hyperreflexia induced by intravesical acidification and that the site responsible for this action is likely to be the dorsal root ganglia.